+0  
 
0
378
1
avatar

fine the equation of a line that passes through (-7, -6) and (3, -6)

 Aug 24, 2017

Best Answer 

 #1
avatar+7350 
+3

First let's find the slope.

 

slope  =  \(\frac{\text{difference of y values}}{\text{difference of x values}}=\frac{-6--6}{-7-3}=\frac{0}{-10}=0\)

 

So, in point-slope form, using the point  (-7, -6) ,  the equation is....

 

y - -6  =  0(x - -7)

 

y + 6  =  0

 

y  =  -6

 

And..we could have noticed from the beginning that the  y  value of both points is  -6  . That means it must be a horizontal line at  y = -6  .  smiley

 Aug 25, 2017
 #1
avatar+7350 
+3
Best Answer

First let's find the slope.

 

slope  =  \(\frac{\text{difference of y values}}{\text{difference of x values}}=\frac{-6--6}{-7-3}=\frac{0}{-10}=0\)

 

So, in point-slope form, using the point  (-7, -6) ,  the equation is....

 

y - -6  =  0(x - -7)

 

y + 6  =  0

 

y  =  -6

 

And..we could have noticed from the beginning that the  y  value of both points is  -6  . That means it must be a horizontal line at  y = -6  .  smiley

hectictar Aug 25, 2017

7 Online Users

avatar